Development of novel MnO2 coated carbon felt cathode for microbial electroreduction of CO2 to biofuels. (1st November 2019) - Anwer, A.H.; Khan, M.D.; Khan, N.; Nizami, A.S.; Rehan, M.; Khan, M.Z.
Abstract: Fabrication of superior and cost-effective cathodic materials is vital in manufacturing sustainable microbial electrolysis cells (MECs) for biofuels production. In the present study, a novel manganese dioxide (MnO2 ) coated felt cathode (Mn/CF) has been developed for MECs using electrodeposition method via potentiostat. MnO2 is considered to encourage exogenous electron exchange and, in this way, improves the reduction of carbon dioxide (CO2 ). MnO2, as a cathodic catalyst, enhances the rate of biofuel production, electron transfer, and significantly reduces the cost of MECs. A maximum stabilized current density of 3.70 ± 0.5 mA/m 2 was obtained in case of MnO2 -coated Mn/CF based MEC, which was more than double the non-coated carbon felt (CF) cathode (1.70 ± 0.5 mA/m 2 ). The dual chamber Mn/CF-MEC achieved the highest production rate of acetic acid (37.9 mmol/L) that was significantly higher (43.0%) in comparison to the non-coated CF-MEC. The cyclic voltammograms further verified the substantial enhancement in the electron transfer between the MnO2 coated cathode and microbes. The obtained results demonstrate that MnO2 interacted electrochemically with microbial cells and enhanced the extracellular electron transfer, therefore validating its potential role in biofuel production. The MnO2 coated CF further offered higher electrode surface area and better electron transfer efficiency, suggesting its applicability in the large-scale MECs. Graphical abstract: Image 1 Highlights: Development of novel manganese oxide (MnO2 ) coated felt cathode (Mn/CF). Microbial electroreduction of CO2 to biofuels using MnO2 coated cathode. Improved biofuel production and extracellular electron transfer. The obtained maximum current density of 3.70 ± 0.5 mA/m 2 Achieved highest acetic acid production using modified electrode.